WORKING ON THE FOUR SKILLS IN TEACHING ENGLISH: AN INTEGRATED APPROACH TO EFFECTIVE LANGUAGE DEVELOPMENT (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Teaching English in contemporary education requires more than delivering grammar rules or vocabulary lists. Effective communication is achieved only when learners can understand and produce language in multiple contexts. This thesis examines the four fundamental language skills—listening, speaking, reading, and writing—and highlights why an integrated approach leads to more successful English language acquisition. Drawing on recent studies and classroom-based research, the thesis discusses theoretical foundations, integrated teaching strategies, challenges encountered in EFL (English as a Foreign Language) settings, and practical implications for educators. The findings suggest that teaching the four skills holistically significantly improves students’ communicative competence, motivation, confidence, and autonomy.